Short communication: Substantial heritability of larval size in the black soldier fly reveals potential for selective breeding - R.M. Zaalberg; L.B. Andersen; L.S. Hansen; G. Gebreyesus; M. Henryon; K. Jensen; H.M. Nielsen (Animal)
An underutilised tool to optimise the production of black soldier fly larvae (Hermetia illucens L.; Diptera: Stratiomyidae) is selective breeding. We validated that larval size is moderately heritable and should, therefore, respond to selection. We tested this premise by estimating additive genetic variation for larval size assessed as individual larval surface area (ISA), group surface area (GSA), and group weight (GW). A full-/half-sib design was used, where one virgin male fly was offered the opportunity to mate four virgin females. Each male had between one and three females that produced larvae, with a mean of 1.85 females per male. For each female that produced larvae, two cups with feed were prepared and fifty larvae were transferred to each cup. On day twelve after egg hatching, thirty larvae (full sibs) from each cup were randomly selected, and ISA was recorded (9 486 larvae from 92 sires and 169 dams). The GW of the thirty larvae was then recorded, and the GSA was calculated from the ISA of the thirty larvae in the group (317 full-sib groups). The data were analysed using sire-dam models including population average and batch as fixed effects and sire, dam and cup as random effects. The results showed moderate heritability for ISA (0.40), with a moderate effect of the common environment (0.21). For GSA and GW, moderate heritabilities were observed (0.39 and 0.30). These results show that there is great potential for black soldier fly breeders to implement selection for bigger larval size in their breeding programmes.